2016
DOI: 10.3748/wjg.v22.i22.5267
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease: A descriptive study of 716 local Chilean patients

Abstract: IBD has continued to increase in the study cohort, slowly approaching the level reported in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 47 publications
2
29
0
8
Order By: Relevance
“…Although, mortality due to IBD is not very high, it still presents a major healthcare burden. It damages the patient's quality of life to a considerable extent due to its onset in early adulthood and chronicity (Simian et al ., ). It enhances the risk of colorectal cancer and possibly is also associated with leukaemia and lymphoma (Wheat et al ., ).…”
Section: Clinical Studies With Curcuminmentioning
confidence: 97%
“…Although, mortality due to IBD is not very high, it still presents a major healthcare burden. It damages the patient's quality of life to a considerable extent due to its onset in early adulthood and chronicity (Simian et al ., ). It enhances the risk of colorectal cancer and possibly is also associated with leukaemia and lymphoma (Wheat et al ., ).…”
Section: Clinical Studies With Curcuminmentioning
confidence: 97%
“…17 As in other studies musculoskeletal manifestations are the most prevalent extra-intestinal manifestations but the percentage of affected patients was higher. 29,30,31 It has been suggested that with the rising of IBD extension the risk of peripheral arthritis increases. 32 Higher incidence of the disease extension correlates with higher musculoskeletal manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Su incidencia ha ido en aumento en países desarrollados, y estudios en países en vías de desarrollo de Sudamérica, África y Asia han demostrado también un aumento significativo de la EII 2 . Aunque la incidencia y prevalencia en Chile aún es desconocida, un estudio ha sugerido un aumento de estas enfermedades 3 . En las últimas décadas, la EII ha surgido como un desafío de la salud pública, debido al aumento de incidencia, a la afectación principalmente del adulto joven y a los costos de su tratamiento 2,4 .…”
unclassified